Transient Heat Transfer - Annaratone, Donatello; SpringerLink (Online service) (London: Springer, 2011)
This book presents a new and direct computational method for transient heat transfer. The approach uses the well-known dimensionless Biot number and a second dimensionless number introduced by the author. The methodology allows for a transient heat transfer calculations without using finite difference programs. The book presents many examples and various tables demonstrating the potential of this new methodology. Many diagrams illustrate the physical phenomena.
Introduction -- General Law of Thermal Conduction -- Heat Diffusion in a Plate of Infinite Thickness -- Heat Diffusion in a Plate of Finite Thickness -- Plate immersed in Fluid -- Plate Heated or Cooled on one Side -- Tube Heated or Cooled on Outside Surface -- Plate Radiated on Both Sides -- Plate Radiated on One Side -- Transient Heat Transfer through a Plane Wall -- Transient Heat Transfer through a Curved Wall (tube).
0
Keywords: Engineering; Hydraulic engineering; Engineering; Engineering Thermodynamics, Heat and Mass Transfer; Engineering Fluid Dynamics